Análisis de los factores de riesgo asociados con las tasas mundiales de muerte súbita cardíaca en niños - Byas, Damien (CorSalud, 2017)
Análisis de los factores de riesgo asociados con las tasas mundiales de muerte súbita cardíaca en niños